Evaluation of services provided to integrated students from the point of view of parents and the administrative system in the integration schools in Lattakia Governorate - آذار عبد اللطيف (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to evaluate the services provided to the integrated students from the point of view of parents and the administrative system in the integration schools in Lattakia Governorate. The study sample consisted of (100) parents and (80) of the administrative staff in the integrating schools. The researcher designed a questionnaire that included four areas: (equipment of the resource room - the adequacy of the teacher and the administrative apparatus - the progress of the educational process and treatment plans - the participation of parents). The results were extracted according to the statistical laws that fit the nature of the research at the significance level (0.05). Among the most important results: the evaluation of the services provided to the integrated students in the merging schools came in the order as follows (equipment of the resource room - the progress of the educational process and treatment plans - the adequacy of the teacher and the administrative body - and finally the participation of parents). There are no statistically significant differences between the mean scores of the sample members on the total score of the research tool according to the educational level variable. There are also statistically significant differences between the averages of the sample members in the areas of educational process progress, treatment plans, and parents' participation, according to the variable number of years the student joined the merging school in favor of 3 years and more. The research ended with a number of suggestions